All-cause and cause-specific mortality in psoriasis patients: a systematic review and meta-analysis - Yang, Yi; Zhang, Qin; Huang, Anning; Zhao, Jinpeng; Yang, Jianren; Wang, Lulu; Xu, Guomei (Frontiers in Immunology, 2025)
ObjectiveThe objective of this meta-analysis is to assess the all-cause and cause-specific mortality in patients with psoriasis.MethodIn accordance with PRISMA guidelines, a systematic search of PubMed, EMBASE, and the Cochrane Library (from inception to March 2025) was conducted. Eligible studies comprised English-language cohort studies comparing mortality risk (HR/OR/RR) in adults with psoriasis versus healthy/non-psoriasis controls. Two reviewers independently screened studies, extracted data, and assessed study quality using the Newcastle-Ottawa Scale. Hazard ratios (HRs) were synthesized using random-effects models in Stata 14.0. Sensitivity analyses, subgroup analyses, and assessments of publication bias (via funnel plots and Egger’s test) were also performed.ResultA total of 20 studies involving 8825989 participants were included. Psoriasis patients demonstrated significantly increased risks of all-cause mortality [HR=1.19, 95% CI (1.11–1.28), P=0.000], cardiovascular mortality [HR = 1.32, 95% CI (1.11–1.58), P = 0.002], infection-related mortality [HR=1.24, 95% CI (1.13–1.36), P=0.000], and suicide mortality [HR=1.50, 95% CI (1.03–2.19), P=0.034]. The risk of mortality due to neoplasms was marginally elevated but not statistically significant [HR=1.05, 95% CI (0.98–1.12), P=0.151]. No significant associations were found for neurological disease mortality [HR=0.96, 95%CI (0.83–1.11), P=0.976] or accident-related mortality [HR=0.91, 95% CI (0.81–1.02), P=0.629]. Sensitivity analysis supports the findings. Subgroup analyses revealed higher all-cause mortality risks in Europe (HR=1.11) and Asia (HR=1.23), as well as an increased risk with greater disease severity (moderate-to-severe: HR=1.44; severe: HR=1.54). No publication bias was detected.ConclusionPsoriasis is associated with an increased risk of all-cause, cardiovascular, infection-related, and suicide mortality, highlighting the need for enhanced monitoring and targeted interventions to prevent adverse outcomes particularly for individuals with severe psoriasis.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251017192, identifier CRD420251017192.